(untitled) (Global Journal of Medical Research, 2023)
The article offers explanation of the cortisol cycle The secretion of cortisol from the adrenal glands starts at 3 am This makes the cortisol level in the blood stream high at the morning which determines our high body energy and immune abilities at the morning After 3 pm the amount of cortisol in the blood starts to drop down fast to prepare us for the night rest and sleep While all other cyclic reactions in the body are ruled by sun light there is no light in 3 am to activate the secretion of cortisol At 3 am our breathing is minimal and this is the time when the majority of people die and the majority of babies are born The Earth has maximum temperature at 3 pm which makes its ionosphere and atmosphere maximally extended and minimum at 3 am Thus it seems that our cycle of breathing is in synchrony with the Earth cycle of breathing and this is what activates the cortisol cycle at 3 am